The Role of Social-Media as a Disseminator of Gender Equality Values for Women - Maulana, Mohammad Irfan; Salstiani, Dwi (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2023)
The purpose of this study is to determine the role of social media as a disseminator of gender equality values for women. The research method used in this research is mixed method with netnography method. Data collection techniques using questionnaires distributed online and structured interviews. The data analysis technique used was multiple linear regression test. The results showed that the role of social media is influential as a disseminator of gender equality values. In data analysis, it is shown that 0.5% of the role of social media has an effect as a disseminator of gender equality values.